TERASING DALAM BUDAYA BARAT DAN TIMUR: POTRET “NYAI” HINDIA BELANDA, ABAD XVII-XX - FX. Domini BB Hera; Daya Negri Wijaya (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
“Nyai” is the concept that refer to native woman (including Chinese and Japanese woman) who life without married relationship with European, Chinese, or Arabian man. However the position of “Nyai” is not accepted by foreigner (commonly western society) and indigenous people (commonly eastern society), but they have important role in the family and social-culture in Hindia Belanda, XVII-XX. Beside the negative image attaching to “Nyai”, they also have positive side in society life as cultural mediator between western and eastern culture. It is giving a chance for “Nyai” to give any cultural influence from one society or group to another. The study can give the reader a lot of understanding about development of sexuality in Nusantara (The past Indonesia) and the point is the study like the basic form to explain the phenomena of unmarried couple today. In short, this study will focus on the image and role of “Nyai” in Hindia Belanda, XVII-XX